2017
DOI: 10.1084/jem.20161950
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the response to CTLA-4 blockade by longitudinal noninvasive monitoring of CD8 T cells

Abstract: Rashidian et al. show that 89Zr-PEGylated single-domain antibodies that target CD8+ T cells can be used to monitor and evaluate the response to immunotherapy as a predictive tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
273
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(283 citation statements)
references
References 43 publications
8
273
0
2
Order By: Relevance
“…Not-surprisingly, stronger infiltration of CD8 + T cells into tumors generally associates with better prognosis; this has been demonstrated in various cancer types such as melanoma (2,3), ovarian (4), colorectal (5), bladder (6), breast (7), and pancreatic (8) cancer. Furthermore, stronger infiltration of CD8 + T cells can predict patient response to standard of care chemotherapy (9)(10)(11) and to immune checkpoint blockade therapy such as anti-CTLA-4 (12) or anti-PD-1 (13,14). Therefore, it is important to characterize the infiltration of CD8 + T cells in solid tumors and mechanisms that regulate this.…”
mentioning
confidence: 99%
“…Not-surprisingly, stronger infiltration of CD8 + T cells into tumors generally associates with better prognosis; this has been demonstrated in various cancer types such as melanoma (2,3), ovarian (4), colorectal (5), bladder (6), breast (7), and pancreatic (8) cancer. Furthermore, stronger infiltration of CD8 + T cells can predict patient response to standard of care chemotherapy (9)(10)(11) and to immune checkpoint blockade therapy such as anti-CTLA-4 (12) or anti-PD-1 (13,14). Therefore, it is important to characterize the infiltration of CD8 + T cells in solid tumors and mechanisms that regulate this.…”
mentioning
confidence: 99%
“…The application of molecular imaging in immuno‐oncology is related to employing radiolabeled antibodies, antibodies fragments, peptides, and proteins to track immune checkpoint targets at the cellular and molecular levels and to uncover the dynamic changes of the biomarkers expression . Preclinical studies showed that immuno‐PET monitoring of CD8+ T cells could serve as a predictive and prognostic biomarker for immune checkpoint therapy . Currently, effective efforts are underway to define PD‐L1 or PD‐1 expression using noninvasive molecular probes, of which a large number of studies focused on the feasibility of antibody‐based tracers in immunotherapy …”
Section: Imaging Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%
“…70 Preclinical studies showed that immuno-PET monitoring of CD8+ T cells could serve as a predictive and prognostic biomarker for immune checkpoint therapy. 71,72 Currently, effective efforts are underway to define PD-L1 or PD-1 expression using noninvasive molecular probes, of which a large number of studies focused on the feasibility of antibody-based tracers in immunotherapy. [73][74][75][76][77][78][79][80][81][82] For PET/CT-based molecular imaging, 64 Cu and 89 Zr are the most common radionuclides used in immuno-oncology.…”
Section: Molecular Imagingmentioning
confidence: 99%
“…OT-I T cells tagged with fluorescently labeled anti-CD8 nanobodies were co-cultured for 4 hours in the presence of antigenic peptide-loaded syngeneic wild-type bone-marrow derived dendritic cells generated from B6 bone marrow (Rashidian et al, 2017;Inaba et al, 1992). The cells were fixed, stained and imaged using confocal microscopy as previously described (Kumari et al, 2015).…”
Section: Microscopy and Image Analysismentioning
confidence: 99%